Evaluation of nerve regeneration in diabetic rats - Salles Jr,Guataçara Schenfelder (2013)
PURPOSE: To compare sciatic nerve regeneration between non-diabetic (control) and streptozotocin-induced diabetic Wistar rats. METHODS:Four subgroups were evaluated. CN: Non-diabetic rats submitted to neurorrhaphy (n=9); DN: Diabetic rats submitted to neurorrhaphy (n=9); CG: Non-diabetic rats submitted to nerve grafting (n=10); DG: Diabetic rats submitted to nerve grafting (n=9). The nerve regeneration was evaluated by walking track analysis (sciatic functional index), electrophysiological test, histomorphometric analysis and triceps surae muscle weight. RESULTS:At 60 days post-surgery, functional recovery of DN was similar to that of the non-diabetic rats (CN, CG), but DG didn't achieve the same. Evoked potential amplitudes showed no statistically significant differences among subgroups. Triceps surae muscle was heavier in CN. No statistically significant differences were observed between the control and diabetes subgroups with respect to histomorphometric analysis. CONCLUSION: After 60 days, DN had a functionally similar recovery to that of the control animals, whereas nerve grafting in diabetic rats didn't allow the same. The muscle atrophy was lower in CN. In the rest of evaluations, as electrophysiological and histomorphometric, diabetic rats were not different from control ones.